"TERRA INCOGNITO" OF SHOKAN UALIKHANOV: TERRA INCOGNITO" OF SHOKAN UALIKHANOV - Gauriyeva, Gulzhan (Журнал иностранных языков и лингвистики, 2025)
Intercultural communication, which has a history of more than a thousand years, has become particularly relevant in the last century and has become an object of a separate science. In practical terms, this is due to the rapid changes in the structure and nature of the population of almost all countries, the extraordinary mobility of many social groups, and therefore communication between representatives of different cultures has become typical, and the communicative effectiveness of communication has become an urgent necessity.